Seasonal variations of cadmium (Cd) speciation and mobility in sediments from the Xizhi River basin, South China, based on passive sampling techniques and a thermodynamic chemical equilibrium model. (1st December 2021) - Gao, Lei; Li, Rui; Liang, Zuobing; Hou, Lei; Chen, Jianyao
Highlights: · Sulfates reduction enabled Cd concentrations to remain at µg·L −1 levels in pore water. · Sulfides oxidation mainly accounted for remobilization of sediment Cd. · Sediment acted as a sink of Cd to water in winter and shifted to a source in summer. · Sediment Cd was released into river and migrated downstream mainly in Cd-S complexes. Abstract: Understanding the speciation and mobilization mechanisms of potentially toxic metals in sediments is critical to aquatic ecosystem health and contamination remediation in urban rivers. In this study, chemical sequential extraction, a thermodynamic chemical equilibrium model (Visual MINTEQ ver. 3.1), diffusive gradient in thin films (DGT), and high-resolution dialysis (HR-Peeper) techniques were integrated to identify seasonal variations in cadmium (Cd) mobility in sulfidized sediments. Acid-soluble Cd was the dominant geochemical fraction in sediments, followed by residual, oxidizable, and reducible Cd. The DGT-labile Cd concentration was associated with various geochemical processes and was independent of the total concentration and geochemical fractionation of Cd in sediments. Sulfate reduction facilitated the formation of insoluble CdS and induced low Cd concentrations in sediment porewater. Sulfide oxidation was principally responsible for lowered porewater pH and elevated Cd concentrations in summer. Strongly acidic conditions promoted release of sediment Cd but might reduce the binding efficiency of Chelex resin gel for dissolved Cd, leading to underestimation of the mobility of sediment Cd. Sediments generally functioned as a sink for Cd in winter and shifted to acting as a source in summer, releasing Cd into the overlying water mainly as Cd-S complexes with high potential to migrate downstream. Graphical abstract: Image, graphical abstract